Information Systems Design and Intelligent Applications Proceedings of Fifth International Conference INDIA 2018 Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Somanah, Radhakhrishna; Yang, Xin-She.; Senkerik, Roman; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book gathers a collection of high-quality peer-reviewed research papers presented at the International Conference on Information System Design and Intelligent Applications (INDIA 2018), which was held at the Universite des Mascareignes, Mauritius from July 19 to 21, 2018. It covers a wide range of topics in computer science and information technology, from image processing, database applications and data mining, to grid and cloud computing, bioinformatics and many more. The intelligent tools discussed, e.g. swarm intelligence, artificial intelligence, evolutionary algorithms, and bio-inspired algorithms, are currently being applied to solve challenging problems in various domains.
Chapter 1: Integrating information technology and marketing for better customer value -- Chapter 2: Use of Social Media for improving student engagement at Université des Mascareignes (UDM) -- Chapter 3: Conceptualising an online resource platform for business students at Université des Mascareignes -- Chapter 4: Development of an Incident Prioritization Model using Fuzzy Logic to Improve Quality and Productivity in IT Support Services -- Chapter 5: Automatic Text-Independent Kannada Dialect Identiﬁcation System -- Chapter 6: HECMI: Hybrid Ensemble technique for Classification of Multiclass Imbalanced data -- Chapter 7: Dolphin Swarm Algorithm for Cryptanalysis -- Chapter 8: A Secured Communication Model for IoT -- Chapter 9: An Exploratory Study of Evidence-Based Clinical Decision Support Systems -- Chapter 10: Modelling the eﬀects of wind farming on the local weather using Weather Research and Forecasting (WRF) model -- Chapter 11: Evaluation of Cloud Computing Adoption using a Hybrid TAM/TOE Model -- Chapter 12: Measuring the influence of moods on stock market using Twitter Analysis -- Chapter 13: Hand Gestures Categorisation and Recognition.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence